Servicios Comerciales de Información: origen y desarrollo (Communication & Society, 1995)
‧This article carries out an extensive review of the reality of Commercial Information Services from their historical beginnings to the present moment. The author stresses the social, cultural, economical, financial, technoÍogical and marketing aspects of these Services, and concludes by pointing out the advantages and inconveniences facing this type of Service in the future. The advantages include references to cost reductions, increased demand and greater specialization, technological advances, less risk of a nonindividualized supply of services and greater freedom, whereas the inconveniences refer to the dangers of vested interest, the invasion of personal privacy, excessive uniformity, a slanted commercial and materialistic view of life and the intromission of public agents. Two dangers are especially visible on the horizon, both to be repected: Capitalistic liberalism, which leads to the concentration of the information market, and State intervention, which would do away with the market itself.